The mediating effect of opportunity recognition on incubated - Entrepreneurial innovation - Niammuad, Damrongrit; Napompech, Kulkanya; Suwanmaneepong, Suneeporn (My University, 2014)
Opportunity recognition plays a central role in the emergence of nascent ventures in entrepreneurship research. The main purpose of this study was to present the mediating effects of opportunity recognition on incubation resources and human capital. Moreover, the study scrutinises the complex inter-relations between opportunity recognition and entrepreneurial product innovation. The data were collected from 389 incubated software start-ups in Thailand and statistically performed by Partial Least Squares Structural Equation Modelling (PLS-SEM). The analysis revealed a persistent impact of the opportunity recognition on the incubation resources and human capital. Opportunity recognition also serves as a significant driver in enhancing entrepreneurial potential to boost new products/services. Interestingly, the study found that the human capital of incubated software entrepreneurs has no significant effect, statistically, on product innovation, against the better judgement of business empires worldwide. © Imperial College Press.
Keywords: Human capital; Incubation resources; Mediating effect; Opportunity recognition; PLS; Product innovation